USP1 (ubiquitin specific peptidase 1) targets ULK1 and regulates its cellular compartmentalization and autophagy. Issue 4 (3rd April 2019) - Raimondi, Marzia; Cesselli, Daniela; Di Loreto, Carla; La Marra, Francesco; Schneider, Claudio; Demarchi, Francesca
ABSTRACT: ULK1 (unc-51 like autophagy activating kinase 1) is a core component at multiple steps of canonical macroautophagy/autophagy. The activity of ULK1 is tightly regulated by several post-translational modifications, including ubiquitination, yet the deubiquitinase (DUB) responsible for its reversible deubiquitination has not been described. Here, we identified USP1 (ubiquitin specific peptidase 1) as a key player in the modulation of ULK1 K63-linked deubiquitination. Moreover, both USP1 depletion and its chemical inhibition by pimozide are coupled to a reduction of ULK1 in Triton X-100 soluble cellular lysates, and its compartmentalization to a fraction that can be solubilized in 5 M urea. In USP1-depleted cells this fraction is also enriched in SQSTM1 (sequestosome 1), the aggresome marker HDAC6 (histone deacetylase 6), and the prototype of USP1 targets FANCD2 (FA complementation group D2). Consistently, in USP1-depleted and pimozide-treated cells, ULK1 forms protein aggregates enriched in SQSTM1, as detected by both immummunofluorescence and co-immunoprecipitation studies. Notably, depletion of USP1 inhibits canonical autophagic flux and promotes an alternative route leading to lysosomal-mediated degradation of SQSTM1. Our findings reveal a novel function of the USP1-ULK1 axis as a modulator of the switch between canonical and unconventional autophagy. Further, we provide the first evidence supporting the existence of a subset of breast tumors co-expressing ULK1 and MAP1LC3B (microtubule associated protein 1 light chain 3 beta) proteins. Because the USP1 inhibitor pimozide affects breast cancer cell growth, targeting USP1 in those tumors relying on autophagy for growth might prove to be a convenient therapeutic strategy. Abbreviations : ATG13: autophagy related 13; BECN1: beclin 1; BZ: bortezomib; CAPN1: calpain 1; DUB: deubiquitinase; FANCI: FA complementation group I; FANCD2: FA complementation group D2; FZR1: fizzy and cell division cycle 20 related 1; HDAC6: histone deacetylase 6; MAP1LC3B: microtubule associated protein 1 light chain 3 beta; PMZ: pimozide; SH3GLB1: SH3 domain containing GRB2 like, endophilin B1; SQSTM1: sequestosome 1; TRAF6: TNF receptor associated factor 6; ULK1: unc-51 like autophagy activating kinase 1; USP1: ubiquitin specific peptidase 1; WDR48: WD repeat domain 48